The potential role of miR-155 in the tumorigenesis of cervical cancer - Chen, Xu; Zheng, Liying; Zeng, Xianxu; Pan, Nanying (Frontiers in Cell and Developmental Biology, 2025)
Cervical cancer poses a major threat to the health of females and is the leading cause of mortality in females. Despite advancements in treatment, most cervical cancer patients have a poor prognosis due to late diagnosis and resistance to treatment. Investigating microRNAs introduces a new path for developing cancer prevention and treatment. miR-155, one of many microRNAs, plays an essential role in tumor development by regulating gene expression processes, such as transcription, translation, and splicing. In cervical cancer, a number of studies have been conducted to exploring the role and mechanisms of miR-155. Therefore, a comprehensive review summarizing all available findings is necessary to clarify the role of miR-155 in cervical cancer development and progression. This review presents an overview of the state-of-the-art research in miR-155 for cervical cancer, including cell apoptosis, migration, invasion, and drug resistance, and highlights its potential as a biomarker and therapeutic target for cervical cancer treatment and prognosis.